Pengaruh Worklife Balance (Keseimbangan Kehidupan Kerja) dan Stres Kerja terhadap Turnover Intention (Keinginan Berhenti Kerja) Karyawan (Studi Kasus di Rumah Sakit Hermina Karawang Tahun 2024) - Ananda, Elfrida Putri; Taufiqurahman, Endang (Jurnal Ilmiah Wahana Pendidikan, 2025)
Turnover intention of R.S. employees Hermina Karawang can be influenced by many factors, including work-life balance and work stress. This research aims to test, analyze and explain the influence of work-life balance and work stress on turnover intention among employees of R.S. Hermina Karawang. This research was carried out using descriptive and verification quantitative methods, namely to find out, analyze and test hypotheses as well as make conclusions and suggestions. Sample determination was carried out using random sampling techniques with a sample size of 150 respondents. The data analysis technique used is a scale range analysis technique and multiple linear regression analysis using SPSS 25. The results of the research show that work life balance, work stress and turnover intention in R.S. employees. Hermina Karawang. Partially, there is a positive and significant influence between work life balance (X1) on turnover intention (Y) of 18.1%, and there is a positive and significant influence between work stress (X2) on turnover intention (Y) of 48.2%. Furthermore, simultaneously there is a positive and significant influence between work life balance (X1) and work stress (X2) on turnover intention (Y) amounting to 59.7% while the remaining 40.3% is influenced by other variables not examined in this research.